Na tela do cinema, a luz da revelação: o imaginário religioso de adolescentes e a mídia cinematográfica - Quintiliano, Angela Maria Lucas (2008)
This study explores transformations in the perceived meaning of life among in a specific group of adolescents. Relations between the traditional institutions (family and school) and the media as established in the socializing process in contemporary western capitalist societies - is correlated with a modification in the production of these meanings. Two concepts were fundamental to the analysis of this shift: the dynamics of the imaginary understood as both reservoir and motor; and mediations understood as "free zones." The study focuses on cinema as the media form best suited for reflection on processes of projection and identification. The methodology is based on qualitative research with data collected from focus groups. The study group consisted of twelve middle class students, between 14 and 17 years of age, in a non-confessional school in the northern area of the city of São Paulo. The chosen film was Constantine. Group interactions revealed a type of discourse that clarify the role of cinematographic media in the construction of the religious imaginary of this group